Ventilator-associated pneumonia caused by carbapenem-resistant Enterobacteriaceae carrying multiple metallo-beta-lactamase genes - Dwivedi Mayank; Mishra Anshuman; Azim Afzal; Singh R; Baronia A; Prasad K; Dhole T; Dwivedi U (Wolters Kluwer Medknow Publications, 2009)
Context: Ventilator-associated pneumonia (VAP) is a leading nosocomial infection in the intensive care unit (ICU). Members of Enterobacteriaceae are the most common causative agents and carbapenems are the most commonly used antibiotics. Metallo-beta-lactamase (MBL) production leading to treatment failure may go unnoticed by routine disc diffusion susceptibility testing. Moreover, there is not much information on association of MBL-producing Enterobacteriaceae with ICU-acquired VAP. Therefore, a study was undertaken to find out the association of MBL-producing Enterobacteriaceae with VAP. Settings: This study was conducted in a large tertiary care hospital of North India with an eight-bed critical care unit. Materials and Methods: The respiratory samples (bronchoalveolar lavage, protected brush catheter specimens and endotracheal or transtracheal aspirates) obtained from VAP patients (during January 2005-December 2006) were processed, isolated bacteria identified and their antibiotic susceptibilities tested as per standard protocols. The isolates of Enterobacteriaceae resistant to carbapenem were subjected to phenotypic and genotypic tests for the detection of MBLs. Results: Twelve of 64 isolates of Enterobacteriaceae were detected as MBL producers, bla IMP being the most prevalent gene. Additionally, in three strains, simultaneous coexistence of multiple MBL genes was detected. Conclusion: The coexistence of multiple MBL genes in Enterobacteriaceae is an alarming situation. As MBL genes are associated with integrons that can be embedded in transposons, which in turn can be accommodated on plasmids thereby resulting in a highly mobile genetic apparatus, the further spread of these genes in different pathogens is likely to occur.